ASSESSING THE EFFICACY OF DUOLINGO FOR ACQUIRING ENGLISH VOCABULARY SKILLS: EXPERIMENTAL RESEARCH - Sari, Lusi Purnama; Hastomo, Tommy; Nurchurifiani, Eva (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2023)
This research aimed to explore the effectiveness of Duolingo on students' vocabulary. The researchers used quantitative methodologies with a quasi-experimental design in this research. This research used two classes that consist of experimental class and the control class as the sample. Class X OTKP served as the experimental class for this study, whereas Class X BDP served as the control class. Forty-six students made up the group. To gather data, the researchers employed multiple-choice vocabulary exams with 40 items. To calculate the data analysis, the researcher used the t-test formula. The finding shows that Ha was approved based on the data analysis. The results showed that ttest 2,8 and ttable = 2,00 with a significance of 5% (0,05) and ttable 2,42 with 1% (0,01). It means that ttest > ttable and Ha was accepted. Therefore, the use of Duolingo is effective for teaching English vocabulary in the tenth grade at SMK Trisakti Jaya Bandar Lampung. Meanwhile, the mean score of students' vocabulary in experimental class is higher than the mean score of students' vocabulary in control class (72.6 > 67,52). The results demonstrate that Duolingo is the solution for the teacher to teach vocabulary at one of Vocational School in Bandar Lampung.